Художньо-семантичне осмислення концепту тиші/мовчання в поетичній палітрі Григорія Чубая - Шарагіна, Ольга; Sharahina, Olga (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті розглянуто поетичні твори Г. Чубая зі збірки «П’ятикнижжя». Здійснено спробу з’ясувати реалі-зацію літературної концепції «тихої лірики» через комунікативні конструкції natural silence – тиші та homo silence – мовчання. Доведено, що герметично-енігматичний субкод тиші/мовчання проявляється в інтимно-особистісній, пейзажно-натуралістичній та автокомунікативній площинах поетичного тексту Г. Чубая. In the article considered the poems from the collection of Gregory Chubay “Pentateuch”. An attempt to clarify the implementation literary concepts “quiet poetry” in poems artist through communication concepts natural silence – silence and homo silence – silence as a means of expressing their own aesthetic positions through a system of individual artistic means, among which stand out: lack of punctuation, free verse (vers libre), good blotches everyday speech and own neologisms. It is proved that the qualitative paradigm concepts silence marked a profound reflection of the internal state lyrical. Language poet riches in refined stylistic tropes and figures and fills implicit images naturalis silentio and homo silentio sacral and enihmatychnym content. Codes voiceless especially important in an intimate and personal, landscape and naturalistic and avtokomunikatyvniy planes Gregory Chubay poetic text.
Art and Semantic Understanding of the Concept of Silence in Poetic Palette Gregory Chubay
Keywords: сімдесятники; «тиха лірика»; natural silence – тиша; homo; silence – мовчання; герметизм; seventies; “quiet poetry”; natural silence – silence; homo silence – silence; hermetism